2021
DOI: 10.7759/cureus.13409
|View full text |Cite
|
Sign up to set email alerts
|

Development of Unity Simulator for Epidural Insertion Training for Replacing Current Lumbar Puncture Simulators

Abstract: We have recently developed the Unity Simulator for Epidural Insertion Training (USEIT) system that provides an innovative and relatively inexpensive virtual simulation approach for epidural training. This report describes the design and development process to produce the USEIT system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…IVE-based anesthesia training has been reported for procedural areas such as bronchoscopy, central line insertion, and regional anesthesia simulators. 17–20 Studies investigating such procedural training have shown that practicing technical skills in virtual environments can lead to effective knowledge acquisition and retention with subsequent successful clinical application. 15,17 Furthermore, IVEs can be easily manipulated, allowing iterative skill-building within evolving virtual scenarios.…”
Section: Ives and Anesthesia Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…IVE-based anesthesia training has been reported for procedural areas such as bronchoscopy, central line insertion, and regional anesthesia simulators. 17–20 Studies investigating such procedural training have shown that practicing technical skills in virtual environments can lead to effective knowledge acquisition and retention with subsequent successful clinical application. 15,17 Furthermore, IVEs can be easily manipulated, allowing iterative skill-building within evolving virtual scenarios.…”
Section: Ives and Anesthesia Educationmentioning
confidence: 99%
“…15,16 IVE-based anesthesia training has been reported for procedural areas such as bronchoscopy, central line insertion, and regional anesthesia simulators. [17][18][19][20] Studies investigating such procedural training have shown that practicing technical skills in virtual environments can lead to effective knowledge Cost for creation and equipment can vary from a few hundred to thousands of dollars, depending on the level of immersion and complexity.…”
Section: Technical Skillsmentioning
confidence: 99%
“…With the development of additive manufacturing, it is quite common to insert it on the haptic interface terminal tool. For instance, in [11], where authors used a Novint Falcon for their epidural simulator, they have developed a custom end effector to substitute the Novint Falcon one (See Fig. 2).…”
Section: Recent Samples Using Commercial Haptic Devicesmentioning
confidence: 99%
“…The originality of this study mainly concerns the methods Fig. 2: Epidural simulator based on a Novint Falcon [11] to compute in real-time the force to be reproduced by the haptic interfaces, taking into account the respiration of the virtual patient.…”
Section: Recent Samples Using Commercial Haptic Devicesmentioning
confidence: 99%
“…The ideal partial task trainer for neuraxial technique training would combine the physical and anatomic fidelity of manikins with the visuospatial feedback advantages and tactile fidelity found in computer-based models. More recently, haptics have been incorporated with virtual reality and gamification features 9,10 in an effort to enhance skill acquisition and trainee motivation. The use of a virtual environment now can achieve a higher degree of fidelity in recreating the clinical environment while retaining the fidelity in the tactile sensation of spinal or loss of resistance technique that haptics can provide.…”
Section: Simulation-based Individual Training and Assessmentmentioning
confidence: 99%